Simultaneous occurrence of multiple types of cutaneous tuberculosis (TVC and PNT) with internal organ tuberculosis (PTB). - Mia, MA; Chowdhury, UA; Ahmed, N; Shafique, M; Islam, N (Mymensingh Medical Journal, 2007)
The abstract of this article is available on the PubMed website. Mymensingh Med J. 2007 Jan;16(1):108-12